2009
DOI: 10.1590/s1983-14472009000400009
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco para doença arterial coronariana em pacientes admitidos em unidade de hemodinâmica

Abstract: ARTIGO ORIGINALFeijó MKEF, Lutkmeier R, Ávila CW, Rabelo ER. Fatores de risco para doença arterial coronariana em pacientes admitidos em unidade de hemodinâmica. Rev Gaúcha Enferm., Porto Alegre (RS) 2009 dez;30(4):641-7. (220, 73%), dislipidemia (150, 50.5%), obesidad (87, 29%), diabetes mellitus (81, 27%), tabaquismo (77, 25.5%), consumo de alcohol (67, 22%) y alimentación pobre en frutas y verduras (15, 5%). La correlación entre el número de FR y las variables analizadas (escolaridad, sueldo mínimo, edad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
1
2
0
10
Order By: Relevance
“…In Brazil, Coronary Artery Disease (CAD) caused more than 100 thousand deaths in 2011 (1) . Several risk factors are associated with CAD, and are significant in all populations, such as smoking, alcohol consumption, hypertension, hypercholesterolemia, obesity, sedentary lifestyle, and low intake of fruits and vegetables (2) . Among cardiovascular disease (CVD), CAD represents the most common cause of cardiac ischemia and may happen in different ways, from angina pectoris to acute myocardial infarction (AMI).…”
mentioning
confidence: 99%
“…In Brazil, Coronary Artery Disease (CAD) caused more than 100 thousand deaths in 2011 (1) . Several risk factors are associated with CAD, and are significant in all populations, such as smoking, alcohol consumption, hypertension, hypercholesterolemia, obesity, sedentary lifestyle, and low intake of fruits and vegetables (2) . Among cardiovascular disease (CVD), CAD represents the most common cause of cardiac ischemia and may happen in different ways, from angina pectoris to acute myocardial infarction (AMI).…”
mentioning
confidence: 99%
“…18 Outro estudo realizado no mesmo estado, em um hospital universitário da cidade de Porto Alegre, identificou que a obesidade foi o quarto fator de risco mais prevalente entre indivíduos com DAC, estando presente em 28,8% da amostra. 21 Estudo de Harris et al 22 relatou risco 50% mais elevado para doenças cardiovasculares entre mulheres com IMC acima de 29, quando comparadas com a população de referência (IMC<21). Além disso, a obesidade esteve associada com hipertrofia miocárdica, independentemente de hipertensão arterial, e com taxas mais altas de insuficiência cardíaca.…”
Section: Resultsunclassified
“…The description of the study participants in regard to the predominance of inactive men who are married or in consensual union is similar to other studies with patients with CAD or who have undergone cardiac catheterization. (15)(16) The presence of various comorbidities considered to be risk factors for cardiovascular diseases, such as hypertension, diabetes, dyslipidemia, and obesity, demand pharmacological adherence for the control of the diseases. (15) In this study, we found the daily mean of 6.8 ±2.1 drugs, and 98 (97%) patients adhered to the drug therapy.…”
Section: Discussionmentioning
confidence: 99%